Is low-value care for persistent musculoskeletal pain more common in rural than urban areas? A scoping review - Kara Harris; Alejandra Lopera-Escobar; Georgina Luscombe; Paulo Ferreira; Carlos Mesa-Castrillon (BMC Health Services Research)
Abstract Background Low-value care refers to the provision of health services that confer little or no benefit to patients, or have the potential to incur unwarranted harms. A breadth of literature exists investigating geographical variations in rates of potential low-value interventions for musculoskeletal pain. This scoping review aimed to examine the provision of low-value care for osteoarthritis and lower back pain by degree of rurality (e.g., urban, rural and remote areas). Methods This scoping review followed the Joanna Briggs Institute (JBI) methodology. Electronic searches were performed on five literature databases with no time frame, language or terminology restrictions. Two independent reviewers screened titles and abstracts, reviewed full papers and extracted data from selected studies using a COVIDENCE-developed data extraction tool. Results After screening, 21 papers were selected. Two of the papers explicitly referenced low-value care while 19 investigated the provision of potential low-value interventions. Hip and knee arthroplasty, knee arthroscopy, inappropriate pharmacotherapy and complementary and alternative medicine, were more common in rural compared to urban areas. Hip and knee arthroplasty (in women), lumbar spinal fusion, spinal imaging and glucosamine use, were less common in remote compared to regional and urban areas. Conclusions There is a higher report of multiple low-value interventions for osteoarthritis and lower back pain in rural compared to urban areas and lower reporting in remote areas. The lack of healthcare services in rural areas may promote low-value care, while geographical isolation in remote areas may limit utilization of both low- and high-value interventions.